The ant genus Rhopalomastix (Hymenoptera: Formicidae: Myrmicinae) in Southeast Asia, with descriptions of four new species from Singapore based on morphology and DNA barcoding - Wang, Wendy Y.; Yong, Gordon W.j.; Jaitrong, Weeyawat (Zootaxa, 2018)
The true diversity of the Asian ant genus Rhopalomastix Forel is poorly understood. We use an integrated approach to review the known species and subspecies of Rhopalomastix in Southeast Asia. Based on morphology and supporting DNA evidence, we recognize six species. We raise two subspecies of R. rothneyi Forel to species rank (R. johorensis Wheeler stat. n, R. javana Wheeler stat. n.), synonymize R. janeti Donisthorpe (syn. nov.) with R. johorensis, and describe four new species from Singapore: R. glabricephala sp. n., R. murphyi sp. n., R. striata sp. n., and R. tenebra sp. n. All six species found in Southeast Asia are distinct from each other based on morphology; morphological delimitation of these species is further supported by and congruent with mOTUs generated from objective clustering of short fragment COI barcodes using the best close match criteria. Different castes and sexes of most species are described, including redescriptions of the queen of R. javana and male of R. johorensis. A key to the Southeast Asian species based on the worker caste is also provided. Variation among sympatric and also geographically distant populations, and the possibilities of cryptic species, are discussed.